Bioclimatic Wisdom in Minangkabau Houses: Case Study of Gadang Jopang Manganti House - Nugroho, Agung Murti (University of Merdeka Malang, 2022)
Bioclimatic architecture is an adaptive design to the equatorial tropical climate through passive cooling strategies. This paper aims to evaluate the bioclimatic wisdom of the Minangkabau houses to formulate passive design knowledge with visual observation techniques and measurement of the air temperature and relative humidity. The visual observation method is used to find the level of application of bioclimatic design. The measurement techniques are used to evaluate the thermal environmental comfort in the case study of the Gadang Jopang Manganti House, Munka, Limapuluh Kota, West Sumatra. The result of bioclimatic wisdom elements in the appropriate Gadang Jopang Manganti house is the orientation of the building mass and openings, placement and form of single dwelling space without partition and big roof space. The living room has a comfortable thermal environment performance indicated by the average comfort air temperature, decreasing air temperature, and a longer comfortable period. The development of a bioclimatic design for the Gadang Jopang Manganti House could be taken by improving naatural cooling or optimizing natural ventilation to remove building’s humidity.